Targeted and Off-Target (Bystander and Abscopal) Effects of Radiation Therapy: Redox Mechanisms and Risk/Benefit Analysis - Jean‐Pierre Pouget; Alexandros G. Georgakilas; Jean‐Luc Ravanat (2018)
Radiation therapy (from external beams to unsealed and sealed radionuclide sources) takes advantage of the detrimental effects of the clustered production of radicals and reactive oxygen species (ROS). Research has mainly focused on the interaction of radiation with water, which is the major constituent of living beings, and with nuclear DNA, which contains the genetic information. This led to the so-called target theory according to which cells have to be hit by ionizing particles to elicit an important biological response, including cell death. In cancer therapy, the Poisson law and linear quadratic mathematical models have been used to describe the probability of hits per cell as a function of the radiation dose. Recent Advances: However, in the last 20 years, many studies have shown that radiation generates "danger" signals that propagate from irradiated to nonirradiated cells, leading to bystander and other off-target effects.